The Development of English Speaking Skills in Community Tourism Using Task-Based Learning with Social Media for Undergraduate Students: English Speaking Skills, Task-Based Learning, Social Media - Buaphan, Wipawee; Thoatho, Savitree (Ubon Ratchathani Journal of Research and Evaluation, 2024)
This research aimed to study the effectiveness of using task-based learning with social media to the develop the English-speaking skills and English reading comprehension of undergraduate students at Sakon Nakhon Rajabhat University who were studying community tourism, and to compare the English-speaking abilities and reading comprehension of these students before and after the study. The study used Experimental Research, Pre-Experimental Designs, and One Group Pretest - Posttest Design. The samples selected by the purposive sample group were the 50 undergraduate students at Sakon Nakhon Rajabhat University who registered for the 2nd semester of 2021 academic year. The data was analyzed to find the mean, standard deviation, and t-test on dependent variables. The research findings were as follows: The efficiency value of the average practice score during study was 84.30 after the study was significantly higher than before the study at .05. The mean post-test score was 89.43 points, which is higher than the specified criteria of 80/80. The average achievement score for English speaking skills for task-oriented communication prior to the study was 12.88, with a standard deviation of 2.93, and after the study 33.72, with a standard deviation of 2.33, from a full score of 40 points. It can be concluded that students successfully developed English speaking skills and English reading comprehension in the community tourism context by using task-based learning with social media.